2019
DOI: 10.3847/1538-4357/ab253b
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Gas Reservoirs of z ∼ 2 Galaxies: A Comparison of CO(1−0) and Dust-based Molecular Gas Masses

Abstract: We test the use of long-wavelength dust continuum emission as a molecular gas tracer at high redshift, via a unique sample of 12, z ∼ 2 galaxies with observations of both the dust continuum and CO(1-0) line emission (obtained with the Atacama Large Millimeter Array and Karl G. Jansky Very Large Array, respectively). Our work is motivated by recent, high redshift studies that measure molecular gas masses (M mol ) via a calibration of the rest-frame 850µm luminosity (L 850µm,rest ) against the CO(1-0)-derived M … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 77 publications
3
77
0
Order By: Relevance
“…Sources are indicated by the 3mm.ID (except 1mm.C07 and 1mm.C14a). The black lines show the best-fit empirical relations from Scoville et al (2016; assuming both a constant and dust-luminosity dependent dust-to-gas conversion factor), while the gray triangles show their calibration sample as well as more recent observations from Kaasinen et al (2019). Figure 10.…”
Section: Dust Continuum Versus Low-j Comentioning
confidence: 98%
“…Sources are indicated by the 3mm.ID (except 1mm.C07 and 1mm.C14a). The black lines show the best-fit empirical relations from Scoville et al (2016; assuming both a constant and dust-luminosity dependent dust-to-gas conversion factor), while the gray triangles show their calibration sample as well as more recent observations from Kaasinen et al (2019). Figure 10.…”
Section: Dust Continuum Versus Low-j Comentioning
confidence: 98%
“…Various studies have shown that the cold dust emission from distant galaxies in the Rayleigh-Jeans (RJ) long-wavelength regime can be used as a reliable tracer of the ISM molecular gas mass, under reasonable assumptions on the dust properties (Scoville et al 2014(Scoville et al , 2016Hughes et al 2017;Kaasinen et al 2019). Although the method comes in different flavors, the dust temperatures are expected to have little effect on the dust content measurements, and it is assumed to be fixed at T d =25 K, which corresponds to the typical value for local star-forming galaxies.…”
Section: A3 Rayleigh-jeans Dust-based Estimatementioning
confidence: 99%
“…However, they point out that a α CO value several times smaller is often assumed for ULIRGs and SMGs, and that such a low α CO would be more appropriate to describe the very nuclear regions. In addition, in Kaasinen et al (2019), where the Scoville et al (2016) relation is exploited to test the use of long-wavelength dust emission as a gas mass tracer, the authors conclude that the main contribution to the uncertainty in the derived molecular masses (from either CO(1-0) or dust continuum) remains the α CO factor. Given this large uncertainty, we additionally derive the gas masses assuming the same Galactic α CO of Scoville et al (2016), in order to provide a range of masses that fairly takes this uncertainty into account.…”
Section: Gas Massmentioning
confidence: 99%